A Note On Linear Regression Functions - Encarnación, Mark (Communications in Statistics"”Theory and Methods (Issue: 3), 1992)
It is shown that if X and Y are jointly distributed random variables such that the regression function of Y on Xis linear and is the inverse of that of X on Y then the joint distribution of X and Y is degenerate, if second moments exist.